2006
DOI: 10.1007/s00246-006-1279-2
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular Nodal Reentrant Tachycardia in Children

Abstract: The purpose of this study was to identify the clinical and electrophysiological characteristics of children with atrioventricular reentry tachycardia (AVNRT) and to define the prognosis and the treatment strategy. Sixty-two children (28 males and 34 females mean age, 10.2 +/- 3.2 years) with AVNRT ("slow-fast" type) were included in the study. Patients were divided into two groups: 47 patients with severe symptoms (group A) and 15 with mild symptoms (group B). The severity of the symptoms was not related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Because of the relatively narrow safety zone in small children, it is not suggested that RFCA for AVNRT or para-Hisian accessory pathway be performed in young patients. 30 Cryoablation, instead of radiofrequency ablation, may be a good alternative to avoid such complications. 31 We also had another patient who developed profound bradycardia during ablation of a left lateral accessory pathway, which was attributed to Bezold-Jarisch reflex.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the relatively narrow safety zone in small children, it is not suggested that RFCA for AVNRT or para-Hisian accessory pathway be performed in young patients. 30 Cryoablation, instead of radiofrequency ablation, may be a good alternative to avoid such complications. 31 We also had another patient who developed profound bradycardia during ablation of a left lateral accessory pathway, which was attributed to Bezold-Jarisch reflex.…”
Section: Discussionmentioning
confidence: 99%
“…18 In comparison with AVRT, patients with AVNRT are more likely to be female, with an age of onset >30 years. 16,[19][20][21] SVT has an impact on quality of life, which varies according to the frequency of episodes, the duration of SVT, and whether symptoms occur not only with exercise but also at rest. 18,22 In 1 retrospective study in which the records of patients <21 years of age with WPW pattern on the ECG were reviewed, 64% of patients had symptoms at presentation, and an additional 20% developed symptoms during follow-up.…”
Section: Page Et Al 2015 Acc/aha/hrs Svt Guideline: Executive Summarymentioning
confidence: 99%
“…It is usually seen in young adults without structural heart disease or ischemic heart disease, and >60% of cases are observed in women. 16 The ventricular rate is often 180 bpm to 200 bpm but ranges from 110 bpm to >250 bpm (and in rare cases, the rate can be <100 bpm). 19 The anatomic substrate of AVNRT is dual AV nodal physiology (Table 2).…”
Section: Atrioventricular Nodal Reentrant Tachycardiamentioning
confidence: 99%
See 1 more Smart Citation
“…6.2.4 Natural history: AVNRT is not life-threatening and patients with minimal symptoms do well without therapy. Female patients are more symptomatic and tend to present with syncope (Drago et al 2006). 6.2.5 Clinical presentation: Symptoms include palpitations, chest pain, heart failure, and shock, and rarely syncope, dependent on the duration of the AVNRT.…”
Section: Work-upmentioning
confidence: 99%